If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2xc + 3 = 10 Reorder the terms: 3 + 2cx = 10 Solving 3 + 2cx = 10 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2cx = 10 + -3 Combine like terms: 3 + -3 = 0 0 + 2cx = 10 + -3 2cx = 10 + -3 Combine like terms: 10 + -3 = 7 2cx = 7 Divide each side by '2x'. c = 3.5x-1 Simplifying c = 3.5x-1
| x-2/4+1/3=x-2x-1/3 | | -7/16x=-14 | | -4x+3(6-2x)=-22 | | 3x/2-4x/3=5x+4/6 | | 80-9x+18=9x+8 | | 16x-8x^2-pi=0 | | 3x+2[x+2]=20-[2x-5] | | 16x-8x^2-3.1415=0 | | (2x+89)+(4x-17)=180 | | 6x-8x^2-3.1415=0 | | 16x-8x^2-3=0 | | 6ln(8x)=42 | | x/5+x/3=x-11/6 | | 5/9+18=32 | | 5(x+5)=7(x-3) | | 8x-5+2=14 | | 2x-2=3x+2+7 | | -144=6(4m+5)-6 | | 1+6(-8r+7)=-101 | | x+20=7x+8 | | 5-4x+6x=17 | | 7(3x-1)= | | A=267 | | 9=-5b-4b | | 7(2x+1)= | | 2k=26 | | -13=-8+v/3 | | x^2-4x-12=20 | | m/11=-14/11 | | 7=r/10 | | 11-43=5(x-1)-7 | | 2x+x+3=12 |